1983
DOI: 10.1177/070674378302800414
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Senile Dementia (Alzheimer Type) and Depression

Abstract: The symptomatology and treatment of the various types of depressions found in Alzheimer patients are briefly described as well as a discussion of some of the interesting theoretical problems that are posed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
1

Year Published

1985
1985
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(75 citation statements)
references
References 8 publications
2
72
1
Order By: Relevance
“…Thus, when rigorous research clinical criteria are employed to obtain a diagnosis of Alzheimer's disease -presumably to make certain the cases were indeed of Alzheimer's disease, a course of action that favours the inclusion of more severe cases -there was no depression in 30 cases of dementia (Knesevich et al 1983). Krai (1983) has considered the significance of depression in Alzheimer's disease. There cannot be any certainty on this point, but it would appear that depression does not carry any prognostic implications and the treatment of the depression by antidepressant drugs with anticholinergic properties does not alter the natural history of Alzheimer's disease.…”
Section: Depression In Dementiamentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, when rigorous research clinical criteria are employed to obtain a diagnosis of Alzheimer's disease -presumably to make certain the cases were indeed of Alzheimer's disease, a course of action that favours the inclusion of more severe cases -there was no depression in 30 cases of dementia (Knesevich et al 1983). Krai (1983) has considered the significance of depression in Alzheimer's disease. There cannot be any certainty on this point, but it would appear that depression does not carry any prognostic implications and the treatment of the depression by antidepressant drugs with anticholinergic properties does not alter the natural history of Alzheimer's disease.…”
Section: Depression In Dementiamentioning
confidence: 99%
“…There cannot be any certainty on this point, but it would appear that depression does not carry any prognostic implications and the treatment of the depression by antidepressant drugs with anticholinergic properties does not alter the natural history of Alzheimer's disease. Krai (1983) also took the opportunity of studying 22 'pseudodements' on follow-up and found that 20 of them had developed progressive dementia, the clinical appearances being that of Alzheimer's disease, and that 11 of these had died. Histological confirmation was available in three of these patients.…”
Section: Depression In Dementiamentioning
confidence: 99%
“…12,21 Follow-up of "depressive pseudodementia" in clinical and in community settings has shown that subsequent irreversible dementia frequently develops in these subjects. 3,11,34,35 It is, of course, difficult to pinpoint the actual onset of most chronic diseases, including AD and depression. We used all available evidence to estimate the date of onset of cognitive and functional manifestations of dementia.…”
Section: Commentmentioning
confidence: 99%
“…Aside from the overlap of symptoms in both illnesses (to be discussed further on) is the suggestion based on findings by a number of groups [9][10][11][12][13] that an earlier psychiatric illness, particularly depression, is a risk factor for Alzheimer's disease. This may be especially important if the depressive episode occurs within two years of the diagnosis of dementia, 14 and might then be considered a "prodrome" of dementia.…”
Section: Etiology Of Depressive Syndromes In Dementiamentioning
confidence: 99%
“…A possible factor facilitating the expression of depressive symptoms in early dementia is the retention of insight into cognitive deterioration, 9,24,32 although contradictory evidence in this regard has been published. [33][34][35] Bungener et al 36 found that loss of control was a significant factor for the development of depressive symptoms and it would seem intuitive that remaining awareness of increasing cognitive deficits might interact with gradual loss of autonomy and control to cause demoralization.…”
Section: Depressive Symptomsmentioning
confidence: 99%